The Theologian as Critic: The Contribution of Tinyiko Sam Maluleke. (26th July 2018) - Ngong, David Tonghou
Abstract: Tinyiko Sam Maluleke is a prolific South African theologian whose work mounts a thoroughgoing critique of the status of Christianity in contemporary sub‐Saharan Africa. Situating his work within its archival context, this article argues that the work of Maluleke emphasizes the vocation of the theologian as critic. The essay looks at some key themes in his work and suggests that Maluleke's critique of African Christianity is soteriological in nature, that is, he questions the role the Christian faith may play in the salvation of (South) Africa.